MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA MELALUI PENDEKATAN RECIPROSAL TEACHING PADA POKOK BAHASAN RELASI DAN FUNGSI DI KELAS VIII-4 SMP NEGERI 1 SIBORONG BORONG TAHUN PELAJARAN 2018/2019 - Ati Nurida Manurung (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
The learning process of Mathematics so far the teacher only uses the lecture learning method, and it is rare to find a teacher applying various methods, for example by using the method of discussion, performance, demonstration in every meeting in class. So that it results in students getting bored / bored quickly and will lead to low student learning outcomes. This study aims to 1) determine the strategy of reciprocal teaching approach, 2) determine the improvement of student learning outcomes in mathematics by applying the reciprocal teaching approach strategy. This research is a Classroom Action Research (PTK). The subjects of this study were students of class VIII-4 SMP Negeri 1 Siborong Borong in the 2018/2019 academic year. which amounted to 34 students. The research was carried out in two cycles. Each cycle consists of 4 stages, namely the planning, action, observation and reflection stages. The research instrument used an observation sheet in the form of a check-list. This study is also equipped with a table of scores from tests conducted by students. Overall the results of the research from the beginning of the action obtained that students who achieved ≥ KKM (34) were completely absent and the completeness was 0%, where the average score of students was 55 of 34 students, 15 students (10.71%) obtained completeness and 25 students (55.88%) which have not been completed. In Cycle I, the average score of students increased to 46.07 where 7 students (25%) obtained completeness, 15 students (75%) who had not completed and the average value of student activity observations was 55.88% in the poor category. In Cycle II the average score of students increased to 75.29 from 34 students, 31 students (92.86%) obtained completeness and 3 students (8.82%) who have not completed and the average value of student activity observations is 80, 88% in the good category. From the classical improvement that has been obtained from each cycle, it can be concluded that the application of a reverse teaching approach strategy (reciprocal teaching) can improve student learning outcomes.